2006
DOI: 10.1074/jbc.m508533200
|View full text |Cite
|
Sign up to set email alerts
|

PS-341 (Bortezomib) Induces Lysosomal Cathepsin B Release and a Caspase-2-dependent Mitochondrial Permeabilization and Apoptosis in Human Pancreatic Cancer Cells

Abstract: PS-341 (bortezomib) is a potent and reversible proteosome inhibitor that functions to degrade intracellular polyubiquitinated proteins. PS-341 induces apoptosis and has shown broad antitumor activity with selectivity for transformed cells. We studied the effect of PS-341 on lysosomal and mitochondrial permeabilization, including the role of caspase-2 activation in apoptosis induction in the BxPC-3 human pancreatic carcinoma cell line. PS-341 induced a dose-dependent apoptosis in association with reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 45 publications
3
54
0
Order By: Relevance
“…Although we did not observe that PS-341 induced other BH3-only proteins by gene expression profile (3), it is possible that PS-341 may induce the accumulation of BH3-only proteins by inhibiting proteasomal degradations in SCC cells. Several studies have reported that PS-341 could induce the level of Bik proteins to promote apoptosis (31)(32)(33). Thus, in the future, it will be interesting to examine whether PS-341 promotes Bik accumulation by inhibiting its degradation in SCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not observe that PS-341 induced other BH3-only proteins by gene expression profile (3), it is possible that PS-341 may induce the accumulation of BH3-only proteins by inhibiting proteasomal degradations in SCC cells. Several studies have reported that PS-341 could induce the level of Bik proteins to promote apoptosis (31)(32)(33). Thus, in the future, it will be interesting to examine whether PS-341 promotes Bik accumulation by inhibiting its degradation in SCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Z-VDVAD-FMK (a chemical inhibitor of caspase-2) or depletion of caspase-2 with an siRNA attenuated MOMP. Thus, caspase-2 emerges as a new link between lysosomal and mitochondrial permeabilization (Yeung et al, 2006). It remains to be determined in which specific circumstances Bid and caspase-2 play predominant roles in mediating post-LMP events such as MOMP.…”
Section: Downstream Signals Leading To Cell Death After Lmpmentioning
confidence: 99%
“…In the case of Bid, caspase-2 can directly cleave full-length Bid to activated tBid (Guo et al, 2002;Bonzon et al, 2006). Caspase-2 activation has been implicated in apoptosis in response to a range of signals, including DNA damage, withdrawal of trophic support, heat shock, treatment with chemotherapeutic agents and tumor necrosis factor-related apoptosis-inducing ligand (Kumar, 1995;Troy et al, 2001;Lassus et al, 2002;Panaretakis et al, 2005;Shin et al, 2005;Bonzon et al, 2006;Yeung et al, 2006;Mhaidat et al, 2007). Caspase-2 has also been shown to associate with CD95 DISC and is activated within this complex but seems not to be essential for CD95-mediated cell death (Lavrik et al, 2006).…”
Section: Introductionmentioning
confidence: 99%